Development of a novel breakfast food product for primary school children in an informal settlement - Kearney, Jeannette Emmarentia (My University, 2013)
A baseline survey on the nutritional status of primary school children was conducted by means of Quantitative Food Frequency Questionnaire (QFFQ) and the 24-Hr recall questionnaires. The questionnaires were distributed by trained fieldworkers and completed by children attending the primary school in this community. The results of the QFFQ and the 24-Hr recall were used to identify nutrient deficiencies in the target group and to design a food product for a school feeding programme targeted to address specific nutritional needs. The aim of this study was to develop a nutritious novel food product that was affordable and appealing to children, rich in energy, protein and micronutrients. Five recipes were originally tested and evaluated. Recipes were theoretically analyzed by using the Dietary Manager program. The three most suitable recipes were chosen. Sensory analysis, by means of a paired preference test was done to determine which of the three products the subjects preferred. The final product developed was a maize meal and whole wheal "vetkoek". The Agricultural Research Council (ARC) laboratory in Irene bio-chemically analysed the velkoek. A second sensory analysis was conducted to evaluate the product for acceptability. A smiley face evaluation sheet was developed for the acceptance testing. The results showed that the majority (65 percent) of the consumers liked the product very much, 18 percent liked the product moderately, and 17 percent found it acceptable, 90 percent found it to be acceptable for inclusion in a school-feeding program. After the sensory evaluation was done a trained microbiologist at the ARC conducted the shelf life testing. A recipe pamphlet was developed and printed in a format that is easily understood by illiterate people. The pamphlet was used by the community workers, who were responsible for preparing the vetkoek. The results indicated that a vetkoek, meeting all the stated criteria can successfully be developed for a school programme
Thesis (M. Tech. (Dept. of Hospitality and Tourism)--Vaal University of Technology.
Keywords: Vetkoek; Nutrition of primary school children; Child nutrition; 613.20830968; Nutrition -- requirements; Breakfast